2019
DOI: 10.3390/app9235077
|View full text |Cite
|
Sign up to set email alerts
|

New Local Drug Delivery with Antibiotic in the Nonsurgical Treatment of Periodontitis—Pilot Study

Abstract: Combination of the classical subgingival instrumentation (scaling and root planing procedure, SRP) with an antibiotic administered to periodontal pockets in a suitable medium is a promising alternative protocol of nonsurgical periodontal treatment. It enables obtaining the long-term minimum drug concentration inhibiting the development of periopathogens. Objectives: Clinical and microbiological evaluation of periodontal pockets two months after single application of a gel containing piperacillin and tazobactam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
3
5
0
Order By: Relevance
“…To our knowledge, the present study is the only clinical trial comparing the clinical and microbiological effects of Gelcide ® vs. a widely used SRD gel and a placebo for severe periodontitis treatment published so far. The present study identified similar improvements in clinical periodontal outcomes in 64 subjects treated with SI with or without a one-time administration of a locally delivered antibiotic at 6 months; as with other trials on LDD, the similarities of the results between test and control groups represent the main issue that has been identified in this research [ 16 , 44 ]. The purpose of the present study was to compare the effects of two locally delivered antibiotic gels (piperacillin plus tazobactam vs. doxycycline) at the end of SI in stage III–IV periodontitis patients.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…To our knowledge, the present study is the only clinical trial comparing the clinical and microbiological effects of Gelcide ® vs. a widely used SRD gel and a placebo for severe periodontitis treatment published so far. The present study identified similar improvements in clinical periodontal outcomes in 64 subjects treated with SI with or without a one-time administration of a locally delivered antibiotic at 6 months; as with other trials on LDD, the similarities of the results between test and control groups represent the main issue that has been identified in this research [ 16 , 44 ]. The purpose of the present study was to compare the effects of two locally delivered antibiotic gels (piperacillin plus tazobactam vs. doxycycline) at the end of SI in stage III–IV periodontitis patients.…”
Section: Discussionsupporting
confidence: 82%
“…The present treatment protocol included one round of application of piperacillin plus tazobactam, in periodontal pockets evaluated at 3–6 months after the application. Similar protocols of one local adjunctive application have been evaluated in the literature [ 16 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations